A community and functional comparison of coral and reef fish assemblages between four decades of coastal urbanisation and thermal stress. Issue 3 (22nd March 2022) - Cook, Katie M.; Yamagiwa, Hirotaka; Beger, Maria; Masucci, Giovanni Diego; Ross, Stuart; Lee, Hui Yian Theodora; Stuart‐Smith, Rick D.; Reimer, James Davis
Abstract: Urbanized coral reefs experience anthropogenic disturbances caused by coastal development, pollution, and nutrient runoff, resulting in turbid, marginal conditions in which only certain species can persist. Mortality effects are exacerbated by increasingly regular thermal stress events, leading to shifts towards novel communities dominated by habitat generalists and species with low structural complexity. There is limited data on the turnover processes that occur due to this convergence of anthropogenic stressors, and how novel urban ecosystems are structured both at the community and functional levels. As such, it is unclear how they will respond to future disturbance events. Here, we examine the patterns of coral reef community change and determine whether ecosystem functions provided by specialist species are lost post‐disturbance. We present a comparison of community and functional trait‐based changes for scleractinian coral genera and reef fish species assemblages subject to coastal development, coastal modification, and mass bleaching between two time periods, 1975–1976 and 2018, in Nakagusuku Bay, Okinawa, Japan. We observed an increase in fish habitat generalists, a dominance shift from branching to massive/sub‐massive corals and increasing site‐based coral genera richness between years. Fish and coral communities significantly reassembled, but functional trait‐based multivariate space remained constant, indicating a turnover of species with similar traits. A compression of coral habitat occurred, with shallow (<5 m) and deep (>8 m) coral genera shifting towards the mid‐depths (5–8 m). We show that although reef species assemblages altered post disturbance, new communities retained similar ecosystem functions. This result could be linked to the stressors experienced by urban reefs, which reflect those that will occur at an increasing frequency globally in the near future. Yet, even after shifts to disturbed communities, these fully functioning reef systems may maintain high conservation value. Abstract : Our study compared coral and fish communities between 1975 and 2018, in Nakagusuku Bay, Okinawa, Japan. Over 43 years of urbanization and thermal stress, coral and fish assemblages changed significantly, but functional trait space was conserved, with both taxa experiencing even turnovers across space. We observed a shift in dominant coral morphology from branching to massive, and a "depth compression" of corals, with the average depths of deep and shallow coral genera compressing towards the mid‐depths.